2023
DOI: 10.3389/fonc.2023.1121838
|View full text |Cite
|
Sign up to set email alerts
|

Towards targeted colorectal cancer biopsy based on tissue morphology assessment by compression optical coherence elastography

Abstract: Identifying the precise topography of cancer for targeted biopsy in colonoscopic examination is a challenge in current diagnostic practice. For the first time we demonstrate the use of compression optical coherence elastography (C-OCE) technology as a new functional OCT modality for differentiating between cancerous and non-cancerous tissues in colon and detecting their morphological features on the basis of measurement of tissue elastic properties. The method uses pre-determined stiffness values (Young’s modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…The stiffness values of mucinous and solid pattern areas were not statistically significantly different (p = 0.29). However, as was described above, visual C-OCE image assessment of these patterns allows for their distinction (Figure 2B), as we have shown previously in a paper [43].…”
Section: Molecular Analysis Of Colorectal Cancer Tissues and Its Corr...supporting
confidence: 66%
See 4 more Smart Citations
“…The stiffness values of mucinous and solid pattern areas were not statistically significantly different (p = 0.29). However, as was described above, visual C-OCE image assessment of these patterns allows for their distinction (Figure 2B), as we have shown previously in a paper [43].…”
Section: Molecular Analysis Of Colorectal Cancer Tissues and Its Corr...supporting
confidence: 66%
“…In our previous studies, we demonstrated the capabilities of C-OCE for highly sensitive imaging of the CRC tissue structure based on the differences in the elastic properties of individual morphological components [42,43]. This research is the next step toward C-OCE application to CRC screening in terms of understanding the relationship between molecular mutations in cancer and their elasticity/stiffness.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations